Efektivitas Bantuan Pemerintah - Silfia Muhaemin Shaleh; Trisna Insan Noor; Lies Sulistyowati; Iwan Setiawan (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2019)
Soybean are national main commodities in legumes, but the production of soybean in the last five years has decreased. Based on the state, the government implemented Assistance Program of Soybean to increase production and income of soybean farmers. This research was conducted at Jatiwaras Village, Jatiwaras Sub-District, Tasikmalaya District, West Java Province. The aim of this research are to analyze effectiveness of Assistance Program of Soybean. This research uses quantitative with survey method. The research sample was taken using Slovin theory and determined simple random sampling, so that was obtained 85 farmers. The data obtained comes from primary and secondary data. Data collection uses observation, interview, literature study and the instrument uses questionnaire techniques. Data analysis was carried out descriptively and using the Likert Scale. This research using Gap Analysis to analyze the effectiviness of the program. The result of GAP Analysis shows value -2,7 > -1, which means Program Upsus Kedelai is in category not good so it is still not effective.